1983
DOI: 10.1302/0301-620x.65b5.6358231
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of human osteosarcoma by antitumour monoclonal antibody

Abstract: Immunoscintigraphy using radioisotope-labelled monoclonal antibody prepared against osteosarcoma 791T cells was used to detect a primary osteosarcoma. The eight-centimetre tumour was detected using rectilinear scintigraphy of 131I-labelled antibodies. Image enhancement was achieved by subtraction of blood-pool radioactivity labelled with technetium-99m. The ratio of tumour to non-tumour uptake of radioactivity (5:1) suggested that antibody targeting of therapeutic agents is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Initially it was shown that antibody localized in a primary osteogenic sarcoma in one patient [6]. In that case, however, localization was confirmed only by gamma-camera imaging of 1311-791T/36 accumulation at the tumour site.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Initially it was shown that antibody localized in a primary osteogenic sarcoma in one patient [6]. In that case, however, localization was confirmed only by gamma-camera imaging of 1311-791T/36 accumulation at the tumour site.…”
Section: Discussionmentioning
confidence: 96%
“…The anti-human osteogenic sarcoma monoclonal antibody 791T/36 labelled with 13iI was previously reported to localize in a primary human osteogenic sarcoma [6]. In the present study, excised turnout from a further osteogenic sarcoma patient undergoing successful imaging with 131I-labelled antibody has been used to establish a xenograft in immunodeprived mice.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This may have been due to the immunosuppressive effects of large tumour burden as a neoadjuvant trial showed promising results indicating a valuable immune response (Durrant et al, 2000a, b;Schwann et al, 2000). As 791T/36 was originally raised against a human osteogenic tumour cell line and was used successfully to image osteosarcomas in vivo (Farrands et al, 1983), we proposed that 105AD7 may be a suitable vaccine for treatment of this disease. Previous experience with colorectal cancer suggested that 105AD7 would be most effective in treatment of patients with minimal residual disease.…”
mentioning
confidence: 99%
“…Investigations have been completed upon osteogenic sarcomas (Farrands et al, 1983) and colorectal carcinomas (Farrands et al, 1982;Armitage et al, 1983;Pimm et al, 1984). In studies on colorectal cancer, autoradiography of tumours resected from patients given 1311-labelled 791T/36 antibody has indicated that the antibody predominantly localizes in stromal elements and secretions within pseudoacini rather than showing a clear cut binding to malignant cells (Armitage et al, 1983).…”
mentioning
confidence: 99%